Study on Dispersion of Carbon Dioxide over the Shrubbery Region - Huiru, Wang; Zhanping, You; Fan, Mo; Bin, Liu; Peng, Han (Frontiers in Energy Research, 2021)
In the Carbon Capture and Storage (CCS) infrastructure, the risk of a high-pressure buried pipeline rupture possibly leads to catastrophic accidents due to the release of tremendous amounts of Carbon Dioxide (CO2). Therefore, a comprehensive understanding of the effects of CO2 dispersion pattern after release from CCS facilities is essential to allow the appropriate safety precautions to be taken. Due to variations in topography above the pipeline, the pattern of CO2 dispersion tends to be affected by the real terrain features, such as trees and hills. However, in most previous studies, the dynamic impact of trees on the wind field was often approximated linear treatment or even ignored. In this paper, a Computational Fluid Dynamics (CFD) model was proposed to predict CO2 dispersion over shrubbery areas. The shrubs were regarded as a kind of porous media and the model was validated against the results from experiment. It was found that shrubbery affected the flow field near the ground, enhancing the lateral dispersion of CO2. The influence of shrub height and porosity on CO2 dispersion is nonlinear. This research provides reliable data for the risk assessment of CCS.